Capillary Rise ‐ Jurin's Height vs Spherical Cap. Issue 1 (18th November 2019) - Gründing, Dirk; Fricke, Mathis; Bothe, Dieter
Abstract: When liquid rises in a capillary, the interface has a shape close to a spherical cap when the Eotvos number is sufficiently small. This assumption is typically used when computing the stationary rise height of the liquid. Considering a continuum mechanical approach it can be shown that the exact shape of a spherical cap is not a solution to the rise problem yet a good approximation. Consequently, the assumption of a spherical cap used in Washburn‐type rise models is justified only for small Eotvos numbers. In this limit, Jurin's height has the largest error.